Utilização de sistemas agrícolas (tangerinas, citrus reticulata) por aves na região de Pilar do Sul, São Paulo - Campolim, Marcelo Gonçalves (Universidade Federal de São Carlos, 2011)
This study aimed to compare environments of mandarin monocultures (Citrus reticulata) (P1, P2, P3, P4) with contiguous forest fragments (F1, F2, F3, F4) in its avifauna composition and dynamics. The point counts methodology was employed, and points were georeferenced 200m far from each other, and distributed along the plantations and fragments. Seven points were sampled each day of field work, remaining ten minutes in each one, recording all individuals seen and / or listen to an unlimited distance. From November 2009 to October 2010 after 6,730 minutes of observations (1970 and 4760 minutes in fragments and plantations respectivelly), we recorded 5978 contacts (1722 and 4256 in the fragments and in the plantations), which sampled 122 species from 43 families and 15 orders ( 73 passerine and 50 non-passerines). Of the 122 sampled species, 50 (41%) were common to both environments, 12 (10%) were found only in plantations and 60 (49%) only in the forest fragments. Generalist species assumed to be living in two studied environments appear to be well adapted in that region (Colaptes campestris, Furnarius rufus, Patagioenas picazuro, Pitangus sulphuratus, Turdus leucomelas, Vanellus chilensis and Zonotrichia capensis), a result of the disturbance of the environment and the intense anthropic interference . Even the species richness in the plantations not exceeding the fragments, one can propose that this is an attractive environment for part of the local avifauna. However, our data show that it is essential to maintaining patches of native vegetation for many species, which remain isolated even into agricultural systems of trees, as the case studied here, and are likely to disappear without the presence of these fragment.
Keywords: Aves - conservação; Avifauna - Pilar do Sul - Ecossistemas agrícolas; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA DE ECOSSISTEMAS